THE USE OF INFORMATION AND EDUCATIONAL ENVIRONMENT TECHNOLOGIES IN FOREIGN LANGUAGE LEARNING AT HIGHER TECHNICAL INSTITUTIONS - Pryshupa, Yuliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article provides a thorough analysis of the application of information and educational environment technologies in the process of foreign languages learning at higher technical education institutions. It describes the experiences of using these technologies, demonstrating that their implementation facilitates learning and creates a comfortable and familiar environment for students. Special attention is given to the nature of language training in technical universities, where the focus is on specialized terminology and professional communication. Information and educational environment technologies enable the integration of foreign language learning with professional disciplines, providing students with the opportunity to acquire language skills within the context of their technical specialization. The author of the article explores the advantages of modern technologies, emphasizing the importance of experience exchange and the dissemination of best practices in foreign language teaching. Participation in digital professional communities enhances awareness and idea exchange, serving as a motivating factor for both teachers and students. Additionally, the article highlights the positive impact of using multimedia resources and online platforms, which make the learning process more interactive, engaging, and productive. It is emphasized that the use of innovative technologies helps overcome language barriers and psychological complexes faced by students and enables continuous learning beyond the traditional classroom setting. The purpose of the study is to provide a theoretical rationale and an analytical review of key conceptual issues related to various digital tools and resources in the information and educational environment of higher technical education institutions, particularly those used in foreign languages learning. Objectives of the study are focused on the scientifically substantiating the concepts of “information and educational environment” and “language training in higher technical education institutions”; and determining the didactic possibilities of modern software products and tools for building an information and educational environment for foreign language learning. Conclusions. Summarizing the results of the study on the use of information and educational environment technologies in learning foreign languages at higher technical education institutions, the author argues that modern technologies help overcome language barriers and psychological complexes often faced by students. Multimedia resources extend the process of learning a foreign language beyond traditional practical classes, ensuring continuity in learning. This not only enables the acquisition of language skills but also fosters creative thinking, self-directed learning, and effective communication in professional contexts. Thus, the use of modern computer technologies in the educational process significantly enhances the quality of education and contributes to the comprehensive development of students in the context of the global information society. The obtained results indicate the achievement of the research objectives.